A Survey of 215 Non-Hemophilic Patients with Inhibitors to Factor VIII - Green, David; Lechner, Klaus (Thrombosis and Haemostasis, 1981)
Information was obtained by questionnaire about 215 nonhemophilic patients who developed inhibitors against factor VIII (antihemophilic factor). The majority of the patients were over 50 years of age, and approximately equal numbers of males and females were reported. Rheumatoid arthritis was present in 8% of the cases, 7% occurred during pregnancy or the post-partum period, and in several there was an association with allergy to penicillin, asthma, “auto-immune” diseases, or malignancy. In 46% of cases, no underlying disorders were identified. Major bleeding was observed in 87 % of patients, and in 22%, death was attributed either directly or indirectly to the presence of the inhibitor.In 11 of 31 patients receiving no therapy other than supportive transfusions of blood or factor VIII concentrate, the inhibitor disappeared after being present for an average duration of 14 months. Corticosteriods were thought to be effective in abolishing the inhibitor in 22 of 45 patients in whom these were the only drugs administered. Twenty-eight patients received azathioprine as well as corticosteriods; in 19, the inhibitor declined or disappeared during treatment. Finally, 80 patients were treated with cyclophosphamide; in 37 there was a favorable outcome. Inhibitors in children and post-partum patients were more likely to disappear spontaneously or with steroid therapy, whereas those in patients with rheumatoid arthritis or other “autoimmune” disorders required treatment with alkylating agents. However, before any specific therapy can be recommended for this disorder, prospective trials of potential therapeutic agents should be conducted in selected subgroups.
Keywords: Factor VIII inhibitors; Circulating anticoagulants; Acquired antibodies to factor VIII